Risk factors for intussusception in childhood gastroenteritis: a nationwide cross-sectional study in Italy (Epidemiology, Biostatistics, and Public Health, 2022)
Background. The aetiology of intussusception is unknown for most of the cases studied, although some associated conditions have been identified. We aimed to clarify the role played by enteric pathogens as potential risk factors for intussusception. Methods. A retrospective review of the records relating to hospitalizations for gastroenteritis with or without concurrent intussusception in Italian children was conducted among children aged